Habsburg Military Conscription and Changing Realities of the Triplex Confinium (16th-18th Centuries) - Lazanin, Sanja (Array, 2000)
The authors examine and statistically elaborate Habsburg Military conscriptions of the paid and unpaid army from 1573 until 1735, analysing the quantity, organisation and development of military structures on the Habsburg side of the Triplex Confinium. The authors are especially interested in how the tactics and strategies of the Imperial powers, which clashed on the Triplex Confinium, particularly those of the Habsburgs, reflect the number of paid and unpaid military formations on the Triplex Confinium. How did those tactics and strategies influence the spatial and quantitative distribution and the quality of armaments of the military along the borderline? Who were the soldiers, with respect to their ethnic background, who were actually engaged in military operations on all three sides of the border? Consequently, the authors also compare source data collected on the Habsburg side to the Ottoman and Venetian circumstances of the time known from printed sources and literature. Extensive source data are sorted in tables at the end of the article.